Association Between Coronary Artery Lesion Severity and Erectile Dysfunction in Stable Coronary Heart Disease Patients - Arif Bowo Kurniawan; Irsad Andi Arso; Nahar Taufiq (ACI (Acta Cardiologia Indonesiana), 2016)
Background: Atherosclerosis is the underlying process of coronary heart disease. Atherosclerosis is preceded by endothelial dysfunction caused by systemic mechanical and chemical stressors that may occur throughout the blood vessels. Recent studies have found the link incidence of atherosclerosis in the coronary arteries and other arteries as well. Erectile dysfunction (ED) is a clinical manifestation might be caused by atherosclerosis in iliac or pudendal artery. Previous studies have established the relationship between coronary artery involvement and the incidence of ED, but the odds of risk has not been well established. Methods: This was an age matched-paired case-control study. Erectile dysfunction in CHD patients who had undergone coronary angiography was checked by IIEF - 5 questionnaire. The severity of coronary artery lesion was assessed with a Syntax score from coronary angiography results. Moreover these results were assessed by a single experienced observer, blind method and were shown consistency test. Then, the risk of coronary artery lesion severity of the ED was analyzed by chi square test using SPSS version 20. Result: There were 86 subjects consist of 57 subjects in the case group and 29 subjects in thecontrol group. Stable CHD patients with high Syntax scores had 2.75 times risk for development of ED compare with low Syntax scores patients (OR : 2.75, 95 % CI : 1.08 to 6.95, p = 0.03). The severity of coronary artery lesions assessed with Syntax scores were not statistically signifi cant as an independent factor as the incidence of ED. Conclusion: Stable CHD patients with higher severity of lesions in coronary artery have a higher risk of erectile dysfunction than patients with lower severity of the lesion but was not statistically significant as an independent factor on the incidence of ED.Keywords: Severity of coronary artery lesions, erectile dysfunction, stable coronary heart disease